19. Mātiro Whakamua: Looking Over the Horizon - Bargh, Maria; MacArthur, Julie (Environmental politics and policy in Aotearoa New Zealand, 2022)
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

18. Te Mana o te Wai: The Modern Politics of Freshwater - Ruru, Jacinta (Environmental politics and policy in Aotearoa New Zealand, 2022)
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

15. Imperialism and Systems of Stuff - Ngata, Tina (Environmental politics and policy in Aotearoa New Zealand, 2022)
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

14. Te Taiao and 'Biodiversity' - Bargh, Maria; Malcolm, Tame (Environmental politics and policy in Aotearoa New Zealand, 2022)
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

11. How to Write a Press Release - Tapsell, Ellen (Environmental politics and policy in Aotearoa New Zealand, 2022)
Environmental Politics and Policy in Aotearoa New Zealand is a comprehensive introduction to confronting some of today's most urgent challenges. Global warming, threats to biodiversity, contamination of waterways and other environmental issues confront today's citizens with critical challenges that are fundamentally political. Power, authority and state action enable current practices - and through politics and policy that power can be harnessed to create a more ecologically sustainable planet. In this book, leading scholars from around Aotearoa introduce students to environmental politics and policy based in this country's unique institutional, cultural and resource context. The text focuses on the key importance of Te Tiriti o Waitangi, the characteristics of the natural environment in Aotearoa and the role of gender dynamics in the distribution of power, before turning to how this unique setting informs and is, in turn, informed by the global context of environmental politics. The authors take a systemic view of environmental politics and governance in New Zealand, addressing the philosophical and ideational debates about who and what matters (both human and non-human), the political institutions that embed and enact these ideas, and how these ideas then manifest in particular arenas - from climate and freshwater to energy and farming. Practical tips - how to make a submission, organise a protest, write a policy brief or a press release - are woven throughout.
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

10. Social Movements and the Environment - Kurian, Priya; Cretney, Raven; Munshi, Debashish; Morrison, Sandra L. (Environmental politics and policy in Aotearoa New Zealand, 2022)
Environmental Politics and Policy in Aotearoa New Zealand is a comprehensive introduction to confronting some of today's most urgent challenges. Global warming, threats to biodiversity, contamination of waterways and other environmental issues confront today's citizens with critical challenges that are fundamentally political. Power, authority and state action enable current practices - and through politics and policy that power can be harnessed to create a more ecologically sustainable planet. In this book, leading scholars from around Aotearoa introduce students to environmental politics and policy based in this country's unique institutional, cultural and resource context. The text focuses on the key importance of Te Tiriti o Waitangi, the characteristics of the natural environment in Aotearoa and the role of gender dynamics in the distribution of power, before turning to how this unique setting informs and is, in turn, informed by the global context of environmental politics. The authors take a systemic view of environmental politics and governance in New Zealand, addressing the philosophical and ideational debates about who and what matters (both human and non-human), the political institutions that embed and enact these ideas, and how these ideas then manifest in particular arenas - from climate and freshwater to energy and farming. Practical tips - how to make a submission, organise a protest, write a policy brief or a press release - are woven throughout.
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

3. Environmental Ideas in Aotearoa - Mutu, Margaret (Environmental politics and policy in Aotearoa New Zealand, 2022)
Environmental Politics and Policy in Aotearoa New Zealand is a comprehensive introduction to confronting some of today's most urgent challenges. Global warming, threats to biodiversity, contamination of waterways and other environmental issues confront today's citizens with critical challenges that are fundamentally political. Power, authority and state action enable current practices - and through politics and policy that power can be harnessed to create a more ecologically sustainable planet. In this book, leading scholars from around Aotearoa introduce students to environmental politics and policy based in this country's unique institutional, cultural and resource context. The text focuses on the key importance of Te Tiriti o Waitangi, the characteristics of the natural environment in Aotearoa and the role of gender dynamics in the distribution of power, before turning to how this unique setting informs and is, in turn, informed by the global context of environmental politics. The authors take a systemic view of environmental politics and governance in New Zealand, addressing the philosophical and ideational debates about who and what matters (both human and non-human), the political institutions that embed and enact these ideas, and how these ideas then manifest in particular arenas - from climate and freshwater to energy and farming. Practical tips - how to make a submission, organise a protest, write a policy brief or a press release - are woven throughout.
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

Not Ceded but Redistributed - Williams, Joe (Sovereignty & indigenous rights: the Treaty of Waitangi in international contexts, 1991)
Keywords: government relations; kāwanatanga; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; tāngata whenua

Chapter 7: Papaki Rua Ngā Tai: Tides of Confluence: Māori and the State - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."–Book jacket.
Keywords: UNDRIP; crown policy; government relations; land tenure; law; mana motuhake; sovereignty; tino rangatiratanga; welfare policies

Chapter 8: Te Ngau o te Tai: The Sting of the Tide: Māori and the Law - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."–Book jacket.
Keywords: government relations; law; mana motuhake; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

Chapter 9: Rongotai: the Roar of the Ride: Māori in Parliament - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."–Book jacket.
Keywords: government relations; kāwanatanga; law; mana motuhake; māori electorates; māori seats; parliament; self-determination; sovereignty; tino rangatiratanga

Chapter 18: The Treaty of Waitangi and Recognition of Tikanga Māori - Mikaere, Ani (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land tenure; law; race relations; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi

Chapter 15: From the Sideline: Tikanga, Treaty Values and Te Papa - Tapsell, Paul (Waitangi Revisited, 2005)
Keywords: bicultural; government relations; history; land tenure; mana whenua; marae; museums; race relations; te papa museum; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty principles

The Wai 262 Claim: A Claim by Māori to Indigenous Flora and Fauna - Solomon, Maui (Waitangi Revisited, 2005)
Keywords: government relations; history; land tenure; race relations; tiriti o waitangi/treaty of waitangi; treaty claims; treaty settlements; waitangi tribunal

Chapter 10: Feast or Famine: Customary Fisheries Management in a Contemporary Tribal Society - Tuuta, Evelyn (Waitangi Revisited, 2005)
Keywords: crown policy; environment; government relations; history; kaitiakitanga; land tenure; māori rights; race relations; rangatiratanga; resource management; tiriti o waitangi/treaty of waitangi

Chapter 11: Recovering Fagin's Ill-Gotten Gains: Settling Ngāti Kahu's Treaty of Waitangi Claims Against the Crown - Mutu, Margaret (Waitangi Revisited, 2005)
Keywords: government relations; history; land tenure; race relations; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Orakei - Kāwharu, Hugh (Waitangi Revisited, 2005)
Keywords: government relations; hapū; history; land tenure; ngāti whatua; political action; race relations; rangatiratanga; tiriti o waitangi/treaty of waitangi; tāngata whenua; waitangi tribunal

Chapter 6: Rangatiratanga and Social Policy - Kawharu, Merata (Waitangi Revisited, 2005)
Keywords: crown policy; education; government relations; hauora; health; history; land tenure; race relations; rangatiratanga; social policy; tiriti o waitangi/treaty of waitangi

Chapter 7: The Treaty of Waitangi and Social Well-being: Justice, Representation, and Participation - Sullivan, Ann (Waitangi Revisited, 2005)
Keywords: crown; elections; government relations; history; land tenure; local government; māori electorates; māori seats; parliament; race relations; social justice; tiriti o waitangi/treaty of waitangi; treaty principles; voting

Chapter 1: Tino Rangatiratanga - Durie, Mason (Waitangi Revisited, 2005)
Keywords: constitution; government relations; history; kotahitanga; land tenure; marae; nationhood; race relations; self-governance; tiriti o waitangi/treaty of waitangi

Chapter Thirteen: New Māori Politics 1990s-2000s - Bargh, Maria (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"–Publisher's information.
Keywords: elections; government relations; history; iwi; iwi chairs forum; kāwanatanga; mana party; māori electorates; māori seats; social conditions; te pāti māori; tikanga | indigenous law; tāngata whenua; voting

Māori Urban Protest Movements - Taonui, Rawiri (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"–Publisher's information.
Keywords: discrimination; foreshore and seabed act 2004; government relations; hikoi ki waitangi; history; kaitiakitanga; land march; māori womens welfare league; nga tamatoa; parihaka; poverty; protest; racism; rangatiratanga; resistance; social conditions; springbok tour protests; takaparawhau bastion point; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; tāngata whenua; urbanisation

Chapter Five – Māori Representation and Participation in National and Local Government Politics - Sullivan, Ann (Indigenous politics: institutions, representation, mobilisation, 2015)
Keywords: ethnic identity; ethnicity; government; government relations; iwi taketake; māori electorates; māori seats; tiriti o waitangi/treaty of waitangi; treaty obligations

Chapter Four: The Treaty of Waitangi in the Postcolonial Era - Walker, Ranginui (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land march; land tenure; post-colonialism; race relations; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Chapter Seventeen: 'As for these blankets, burn them' Māori and Indigeneity - Hokowhitu, Brendan (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"–Publisher's information.
Keywords: government relations; history; identity; indigenous rights; pan-indigenous movement; social conditions; tikanga | indigenous law; tāngata whenua